A trend of dropping anti‐SARS‐CoV‐2 plaque reduction neutralization test titers over time in Canadian convalescent plasma donors. Issue 5 (18th March 2021) - Drews, Steven J.; Devine, Dana V.; McManus, Janet; Mendoza, Emelissa; Manguiat, Kathy; Wood, Heidi; Girardin, Roxie; Dupuis, Alan; McDonough, Kathleen; Drebot, Michael
Abstract: Background: Convalescent plasma products are a potential passive immunotherapy for Coronavirus disease 2019 (COVID‐19) disease. Various approaches have been utilized to determine the concentration of Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2)‐neutralizing antibodies in plasma products. The Canadian Blood Services used Plaque Reduction Neutralization Test 50 (PRNT50) ‐generated values to qualify convalescent plasma donations supporting clinical trials in Canada. This manuscript describes changes in PRNT50 titers of repeat male plasma donations collected approximately 1–4 months after onset of COVID‐19 signs and symptoms in donors. Study Design and Methods: Men were eligible to donate if they: met standard criteria, were < 67 years of age, reported a previous SARS‐CoV‐2‐positive nucleic acid test, and recovered and were symptom free for at least 28 days prior to donation. Repeat donation analysis required at least one original and one repeat donation where a PRNT50 was performed. Results: From April 29, 2020 to July 25, 2020, 156 donors donated once, with 78 (50%) of the donated plasma having PRNT50 titers of ≥1:160. Thirty‐seven (23.7%) of the donated plasma had a titer of 1:40 or 1:80 (individuals donating this plasma were asked to donate a second time only). A total of 30 donors (19.2%) had repeat donations. Of the repeat donors, 15 (50%) had at least an eightfold change from peak to trough PRNT50 titers within greater than 90 days after onset of COVID‐19 symptoms. Conclusions: Blood operators cannot infer that SARS‐CoV‐2 PRNT50 will remain high in repeat plasma donors 3–4 months after onset of COVID‐19 symptoms.